1973
DOI: 10.1136/hrt.35.6.643
|View full text |Cite
|
Sign up to set email alerts
|

New approach to catheterization of the heart in infants and children.

Abstract: The peripheral blood vessels of infants and children are difficult to cannulate and to repair. The lumen will accommodate only small bore catheters and these are harder to manoeuvre, and impair the quality of angiograms. Lengthening of the procedure and an increase in the amount of contrast medium which is needed both contribute to the morbidity. To our knowledge, cannulation of the internaljugular vein and/or carotid artery for purpose of heart catheterization in humans has never been reported. The technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Diagnostic cardiac catheterization via carotid cutdown in pediatric patients was first performed in the 1960s by Azzolina et al, 2 although this approach did not gain wide acceptance at that time. In the 1970s, percutaneous sheath catheterization was developed and was found to have a lower incidence of arterial complications compared with the arterial cutdown technique, and the femoral arterial route became the favored approach for retrograde left heart catheterization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic cardiac catheterization via carotid cutdown in pediatric patients was first performed in the 1960s by Azzolina et al, 2 although this approach did not gain wide acceptance at that time. In the 1970s, percutaneous sheath catheterization was developed and was found to have a lower incidence of arterial complications compared with the arterial cutdown technique, and the femoral arterial route became the favored approach for retrograde left heart catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…Patient characteristics, including age and weight at time of procedure, cardiac diagnosis, and indication for the catheterization were reviewed. The primary indication for PCA was one of the following factors: (1) low patient weight (with weight <2.5 kg thought by the authors to be at highest risk for vessel trauma from femoral artery catheterization), (2) angle of approach for intervention (all interventions across the aortic valve, and some interventions on the arterial duct or on Blalock-Taussig [BT] shunts were deemed to be best approached by PCA), and (3) need for left heart intervention when both femoral arteries were occluded. When available, the following data Background-Surgical cutdown for access to the common carotid artery provides a more direct route for certain pediatric cardiac interventions and avoids femoral artery injury in small infants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, complex catheter‐based interventions are occasionally best approached from the CA. While the surgical cutdown of the CA with surgical assistance has been well described there is little description in the literature regarding the fate of the CA following surgical cutdown. Importantly, a review of such patients was published by Borghi et al and found that in 1/3 of patients, important CA stenosis or complete occlusion followed surgical cutdown .…”
Section: Discussionmentioning
confidence: 99%
“…of technical difficulties and vascular complications consequent upon the use of the femoral or umbilical arteries as the conduit for the catheter. 9 ' 16 In 1973, Azzolina et al 17 described the use of the carotid artery for diagnostic pediatric catheterization. In 1990, Fischer et al 18 first reported cutting down on the right common carotid artery as a means of achieving balloon dilation of the stenotic aortic valve in neonates.…”
mentioning
confidence: 99%